1990
DOI: 10.2307/2261120
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Man and Climate on Frequency of Fire in the Interior Wet Belt Forest, British Columbia

Abstract: (1) The effects of man and climate on fire frequency have been studied using historical data and a fire-history model in Glacier National Park in British Columbia, Canada. (2) Glacier National Park experienced a change in fire cycle in the 1760s, which could be related to the occurrence of the Little Ice Age. Before 1760, the fire cycle was 80 years and after 1760 it was 110 years. The longer fire cycle after 1760 was clearly related to the cooler, moister climate which also resulted in the advance of glaciers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 14 publications
1
66
1
1
Order By: Relevance
“…Both the Little Ice Age (ca AD 1500-1850) and the Medieval Warm Period (ca 1100-1400) showed great variability of arid and wet periods (Luckman 2000;Tian et al 2006), with variable associated fire regimes. Johnson et al (1990), Johnson & Larsen (1991), Reed (2000) and Weir et al (2000) found changes in fire frequency within the Little Ice Age. Thus, a warmer world need not necessarily be considered a world with more fire activity in the boreal forest of North America.…”
Section: Discussionmentioning
confidence: 95%
“…Both the Little Ice Age (ca AD 1500-1850) and the Medieval Warm Period (ca 1100-1400) showed great variability of arid and wet periods (Luckman 2000;Tian et al 2006), with variable associated fire regimes. Johnson et al (1990), Johnson & Larsen (1991), Reed (2000) and Weir et al (2000) found changes in fire frequency within the Little Ice Age. Thus, a warmer world need not necessarily be considered a world with more fire activity in the boreal forest of North America.…”
Section: Discussionmentioning
confidence: 95%
“…Railways have often been related to accidental or negligence fires due to braking trains, broken brake shoes as well as repair works along railway tracks (Johnson et al 1990, Cardille et al 2001, Arndt 2007, Martinez et al 2009). On one hand, Cardille et al (2001) assume that railroad density is influencing the ignition potential and frequency.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases Marston Bates [31] in his The Forest and the Sea, and Peter Mattheissen [6] in his Wildlife in America, described these relationships. The buildup of fire fuel and the question of fire prevention as opposed to natural regimes have been studied by Johnson et al [32] in British Columbia. Their study found that in contradiction to the idea that fire suppression was responsible for fire frequency and intensity, they found the fire history to be a natural regime.…”
Section: Fire Suppression and Prescribed Burnsmentioning
confidence: 99%